Extent and character of circadian gene expression in Drosophila melanogaster: Identification of twenty oscillating mRNAs in the fly head. - van Gelder, R.N.; Bae, H.; Palazzolo, M.J.; Krasnow, M.A. (Current Biology, 1995)
Although mRNAs expressed with a circadian rhythm have been isolated from many species, the extent and character of circadianly regulated gene expression is unknown for any animal. In Drosophila melanogaster, only the period (per) gene, an essential component of the circadian pacemaker, is known to show rhythmic mRNA expression. Recent work suggests that the encoded Per protein controls its own transcription by an autoregulatory feedback loop. Per might also control the rhythmic expression of other genes to generate circadian behavior and physiology. The goals of this work were to evaluate the extent and character of circadian control of gene expression in Drosophila, and to identify genes dependent on per for circadian expression.A large collection of anonymous, independent cDNA clones was used to screen for transcripts that are rhythmically expressed in the fly head. 20 of the 261 clones tested detected mRNAs with a greater than two-fold daily change in abundance. Three mRNAs were maximally expressed in the morning, whereas 17 mRNAs were most abundant in the evening--when per mRNA is also maximally expressed (but when the flies are inactive). Further analysis of the three 'morning' cDNAs showed that each has a unique dependence on the presence of a light-dark cycle, on timed feeding, and on the function of the per gene for its oscillation. These dependencies were different from those determined for per and for a novel 'evening' gene. Sequence analysis indicated that all but one of the 20 cDNAs identified previously uncloned genes.Diurnal control of gene expression is a significant but limited phenomenon in the fly head, which involves many uncharacterized genes. Diurnal control is mediated by multiple endogenous and exogenous mechanisms, even at the level of individual genes. A subset of circadianly expressed genes are predominantly or exclusively dependent on per for their rhythmic expression. The per gene can therefore influence the expression of genes other than itself, but for many rhythmically expressed genes, per functions in conjunction with external inputs to control their daily expression patterns.